On the genus Diadocidia (Diptera, Sciaroidea, Diadocidiidae) in Australia - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2007)
The first two Australian species of the genus Diadocidia Ruthe, macrosetigera sp. n. and queenslandensis sp. n., are described from Queensland. Both species are assigned to the subgenus Adidocidia Laštovka & Matile. As structures of the male terminalia suggest, the two Australian species are only distantly related to one another, whereas queenslandensis shows definite affinities to D. (A.) papua Ševčík from Papua New Guinea.